Factors restricting oil palm settlers towards Malaysian Sustainable Palm Oil (MSPO) certification / Muhammad Rizwan Abdawa - Abdawa, Muhammad Rizwan (2019)
The oil palm settlers have imposed to follow the sustainability requirement in the oil palm plantation to ensure the stop of the deforestation activities that can lead to the loss of biodiversity, climate change and the increasing of temperature. However, most oil palm settlers in palm oil producing countries are not involved in the oil palm certification scheme such as Malaysian Sustainable Palm Oil (MSPO) Certificate. This study was conducted to identify the factors restricting oil palm settlers towards Malaysian Sustainable Palm Oil (MSPO) certification. This study covers knowledge, cost and financial, management and handling as an independent variable. A total of 52 respondents from oil palm settlers and staff at Felda Umas 4, Tawau, Sabah was taken by using the distribution of the structural questionnaire. All the data from the survey have been collected and analysed through descriptive analysis, factor analysis, Spearmen’s correlation analysis and multiple regression analysis. Results showed that all the variables were a strong positive relationship between all the factors restricting oil palm settlers and settler’s acceptance towards Malaysian Sustainable Palm Oil (MSPO) Certification. Further analysis showed that management and handling is the main factor that contributes to the oil palm settlers face a problem to fulfil the criteria of Malaysian Sustainable Palm Oil (MSPO) certification. Therefore, exposure to new technology encourages oil palm settlers to increase their yield, enhance sustainability, access market, and to achieve certification.